PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Astriani, Nurullita; Dhana, Muhammad Bayu Al (FKIP Universitas Al Washliyah Medan, 2024)
Understanding concepts is one of the goals of mathematics learning. Understanding mathematical concepts is not just knowing a concept, but being able to re-express the concepts studied in a form that is easier to understand and being able to apply them in problem solving. Students' ability to understand mathematical concepts will be formed systematically if students can construct their mathematical knowledge and connect it to contextual problems. One effort that can be made to improve students’ ability to understand mathematical concepts is to apply the Contextual Teaching and Learning approach. This research aims to determine the effect of the Contextual Teaching and Learning approach on students' ability to understand mathematical concepts. This research is a quasi-experimental research. This research was carried out at SMP Negeri 1 Pangkalan Susu. The sample selection technique used in this research is purposive sampling technique. The population of this study were all class VII students. The samples in this study were 2 classes, namely class VII-4 which was used as the experimental class and class VII-5 which was used as the control class. The results of this research show that there is an influence of the Contextual Teaching and Learning approach on students' ability to understand mathematical concepts.